Caracterización Geohidrológica con tomografía eléctrica del parqueadero de la Universidad Antonio Nariño sede Usme - Paula Andrea, Triana Uribe; Alejandra, Piamba Sapuyes (Universidad Antonio Nariño, 2022)
In the locality of Usme seeks to generate and strengthen organizational and construction processes, a project called “New Usme Strategic Operation – Axis of Integration Llanos” was established, where several partial plans were established, in the case of polygon 3 of the Zonal Development Plan, which corresponds to the location of the Antonio Nariño University, the partial plan “ecological technology park” was generated, to support the growth of the locality. In order to contribute geophysical studies to the existing documents on the soil of the University, the realization of this research project aims to characterize the soil of a part of the University Antonio Nariño, specifically the area of the parking lot, using two resistivity methods, Wenner and Schlumberger Vertical Electric Sounding, by means of electric tomography: In both the Wenner and Schlumberger methods, four lines 120 m long each, 16.6 m and 40 m deep respectively were studied. From the information obtained, it was concluded that groundwater is present in layers 2 and 4 of the first borehole, layers 3, 4 and 5 of the second borehole, layers 1, 2, 4 and 5 of the third borehole and layers 1 and 2 of the fourth borehole, as well as that the composition of the first 9 m of soil is mostly saturated clay followed by unsaturated clay and unsaturated gravel, the composition up to 40 m depth varies between fractured rocks, saturated and unsaturated silt